Inkontinensia, Tugas Keluarga, TUGAS KELUARGA DALAM MENGHADAPI INKONTINENSIA URINE PADA LANSIA - Neva Wilis (Jurnal Keperawatan Malang, 2018)
Abstract The main complaint incontinence be on elderly. Many elderly conssider incontinence as the process normal aging, that makes up most elderly refuseed to discuss this. Hence a support the family is essential to solve the problems. The purpose of this research to know the family in the face of incontinence urine on elderly in the village of sumber ngepoh RW 011 in lawang malang district. It research uses the descriptive with a population of households with family members elderly in the village of sumber ngepoh RW 01. The sample used technique total of sampling, and obtained 3 respondents. Variable neasured 5 the family. Study was conducted on 10-16 july 2017. Measuring insrument use is a questionnaire number 15 about, and analysis of using prosentase. Research results as follows, a duty family to know health problems every family members most (69,7%) less. The family to decide for doing a proper act for most (60,6%) less. The family tooffer treaatment members sick almost entirely (81,8%) less. The family home in defending the lucrative health and the development of personality family members most (60,6%) less. Family duty in maintaining a reciprocal relation between a family and health institutions almost entirely (87,8%)less. This research result expected family pay more attention ti tthe health of members of her family. The family can know understanding, the cause of, the types of care incontinence urine, so that it can care for seniors incontinence urine home. Keywords : Incontinence Urine, Thee Task of The Family, The Concept of Elderly.